Ursodeoxycholic acid after bile duct stone removal and risk factors for recurrence: a randomized trial. (26th January 2016) - Yamamoto, Ryuichi; Tazuma, Susumu; Kanno, Keishi; Igarashi, Yoshinori; Inui, Kazuo; Ohara, Hirotaka; Tsuyuguchi, Toshio; Ryozawa, Shomei
Abstract: Background: Currently, no established pharmacologic treatment exists for the prevention of recurrent common bile duct (CBD) stones. Methods: Here, we present a multi‐center randomized trial that compared the CBD recurrence rate after bile duct stone removal between patients given ursodeoxycholic acid (UDCA) and the untreated group. A total of 36 patients were randomly assigned to either the UDCA ( n  = 15) or the untreated group ( n  = 21). The primary end‐point was the recurrence rate of CBD stones. Results: The recurrence rate of CBD stones was 6.6% in the UDCA group and 18.6% in the untreated group ( P  = 0.171). A multivariate analysis found that not receiving UDCA was an independent risk factor for stone recurrence. The recurrence rates of CBD stones did not differ by sex, past history of cholecystectomy, or the presence of gallstones. Conclusions: Our findings indicate that UDCA may be a novel treatment strategy to prevent the recurrence of CBD stones. However, further evaluation of UDCA in a larger number of subjects will be required to confirm the applicability of these results. Abstract : Highlight To address the lack of an established pharmacologic treatment, Yamamoto and colleagues set out to assess the efficacy of ursodeoxycholic acid in preventing recurrence of common bile duct stones after endoscopic removal in a multi‐center ramdomized trial. Their findings indicate that ursodeoxycholic acid administration is a promising preventive treatment strategy.